Clinical and parasitological factors in parasite persistence after treatment and clinical cure of cutaneous leishmaniasis. - Alvaro J Martínez-Valencia; Carlos Frisherald Daza-Rivera; Mariana Rosales-Chilama; Alexandra Cossio; Elkin J Casadiego Rincón; Mayur M Desai; Nancy Gore Saravia; María Adelaida Gómez (Public Library of Science (PLoS), 2017)
The determinants of parasite persistence or elimination after treatment and clinical resolution of cutaneous leishmaniasis (CL) are unknown. We investigated clinical and parasitological parameters associated with the presence and viability of Leishmania after treatment and resolution of CL caused by L. Viannia.Seventy patients who were treated with meglumine antimoniate (n = 38) or miltefosine (n = 32) and cured, were included in this study. Leishmania persistence and viability were determined by detection of kDNA and 7SLRNA transcripts, respectively, before, at the end of treatment (EoT), and 13 weeks after initiation of treatment in lesions and swabs of nasal and tonsillar mucosa.Sixty percent of patients (42/70) had evidence of Leishmania persistence at EoT and 30% (9/30) 13 weeks after treatment initiation. A previous episode of CL was found to be a protective factor for detectable Leishmania persistence (OR: 0.16, 95%CI: 0.03-0.92). kDNA genotyping could not discern differences between parasite populations that persisted and those isolated at diagnosis.Leishmania persist in skin and mucosal tissues in a high proportion of patients who achieved therapeutic cure of CL. This finding prompts assessment of the contribution of persistent infection in transmission and endemicity of CL, and in disease reactivation and protective immunity.